Use of the calibration approach in confidence intervals for mean response times of an open queueing network with feedback. (June 2015) - Gedam, Vinayak K; Pathare, Suresh B
To construct various confidence intervals of mean response times for an open queueing network model with feedback, the calibration approach is used. In this paper, a data-based recurrence relation is used to compute a sequence of response times. Sample means from those response times are used to estimate true mean response times. With the help of numerical simulation study, we investigate the accuracy of the different calibrated confidence intervals of mean response times by calculating the coverage percentage and average length.